Pelaksanaan Bimbingan Belajar Ehipassiko Foundation di Kabupaten Semarang - Wahyuni, Meta Setiya; Kustiani, Kustiani; Widiyono, Widiyono (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2018)
Abstract This study aims to determine the process of implementing Ehipassiko Foundation tutoring at Vidyaloka Temple, Semarang Regency. Tutoring is attended by students from various levels of education and religion, and their implementation at the temple. This research uses descriptive qualitative method. Data collection techniques and instruments use interviews, observation, and documentation. The validity of the data obtained is guaranteed by prolonged engagement, persistent observation, triangulation, and member check. Data analysis uses the Miles and Huberman method which includes data collection (data collection), data reduction (data reduction), data display (data display), and conclusion or verification (conclusion drawing verification). The results of this study include three things, namely (a) the process of implementing tutoring, (b) the role of the mentor teacher, and (c) the impact of tutoring. The process of implementing tutoring consists of three stages, namely before (students prepare a place before learning begins, sometimes before the supervising teacher arrives), when (students who do not need guidance, study independently, students who need help contacting the tutor teacher), and after implementing tutoring (helping teachers clean the room). There are three roles of guidance teachers in the implementation of tutoring. that is, as an educator (the teacher is a role model, namely speaking in front of the altar, followed by Buddhist students), facilitator (the teacher conditions that the learning process is student-centered), and motivators (the teacher corrects and gives value to the student's work). Ehipassiko Foundation tutoring has an impact on increasing cognitive domains (increasing student ranks), affective (appearing discipline, cooperation, etc.), and psychomotor (increasing students' creativity in drawing and coloring). Abstrak Penelitian ini bertujuan untuk mengetahui proses pelaksanaan bimbingan belajar Ehipassiko Foundation di Wihara Vidyaloka Kabupaten Semarang. Bimbingan belajar diikuti oleh siswa dari berbagai tingkatan pendidikan dan agama, dan pelaksanaannya di wihara. Penelitian ini menggunakan metode kualitatif deskriptif. Teknik dan instrumen pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Keabsahan data yang diperoleh dijamin dengan perpanjangan keterlibatan (prolonged engagement), ketekunan dan kegigihan (persistent observation), triangulasi, dan member check. Analisis data menggunakan metode Miles and Huberman yang meliputi pengumpulan data (data collection), reduksi data (data reduction), penyajian data (data display), dan penarikan kesimpulan atau verifikasi (conclusion drawing verification). Hasil dari penelitian ini meliputi tiga hal, yaitu (a) proses pelaksanaan bimbingan belajar, (b) peran guru pembimbing, dan (c) dampak bimbingan belajar. Proses pelaksanaan bimbingan belajar yang terdiri dari tiga tahapan, yaitu sebelum (siswa menyiapkan tempat sebelum pembelajaran dimulai, kadang sebelum guru pembimbing datang), saat (siswa yang tidak memerlukan bimbingan, belajar secara mandiri, siswa yang membutuhkan bantuan menghubungi guru pembimbing), dan setelah pelaksanaan bimbingan belajar (membantu guru membersihkan ruangan). Terdapat tiga peran guru pembimbing dalam pelaksanaan bimbingan belajar. yaitu sebagai seorang pendidik (guru sebagai teladan yaitu ber-namaskara di depan altar, kemudian diikuti oleh siswa beragama Buddha), fasilitator (guru mengondisikan bahwa proses pembelajaran berpusat pada siswa), dan motivator (guru mengoreksi dan memberi nilai pada pekerjaan siswa). Bimbingan belajar Ehipassiko Foundation berdampak pada meningkatnya ranah kognitif (ranking siswa meningkat), afektif (muncul sikap disiplin, kerja sama, dan lain sebagainya), dan psikomotor (meningkatkan kreativitas siswa dalam hal menggambar dan mewarnai).